A seismological overview of the induced earthquakes in the Duvernay play near Fox Creek, Alberta. Issue 1 (18th January 2017) - Schultz, Ryan; Wang, Ruijia; Gu, Yu Jeffrey; Haug, Kristine; Atkinson, Gail
Abstract: This paper summarizes the current state of understanding regarding the induced seismicity in connection with hydraulic fracturing operations targeting the Duvernay Formation in central Alberta, near the town of Fox Creek. We demonstrate that earthquakes in this region cluster into distinct sequences in time, space, and focal mechanism using (i) cross‐correlation detection methods to delineate transient temporal relationships, (ii) double‐difference relocations to confirm spatial clustering, and (iii) moment tensor solutions to assess fault motion consistency. The spatiotemporal clustering of the earthquake sequences is strongly related to the nearby hydraulic fracturing operations. In addition, we identify a preference for strike‐slip motions on subvertical faults with an approximate 45° P axis orientation, consistent with expectation from the ambient stress field. The hypocentral geometries for two of the largest‐magnitude ( M 4) sequences that are robustly constrained by local array data provide compelling evidence for planar features starting at Duvernay Formation depths and extending into the shallow Precambrian basement. We interpret these lineaments as subvertical faults orientated approximately north‐south, consistent with the regional moment tensor solutions. Finally, we conclude that the sequences were triggered by pore pressure increases in response to hydraulic fracturing stimulations along previously existing faults. Key Points: The new seismicity near Fox Creek is clustered in time and space Clusters are induced by hydraulic fracturing of the Duvernay Formation Strike‐slip motion with two clusters confirmed on north‐south fault orientations